Fasting mimicking diet during neo-adjuvant chemotherapy in breast cancer patients: a randomized controlled trial study - Bahrami, Alireza; Haghighi, Shirin; Moghani, Mona Malekzadeh; Khodakarim, Nastaran; Hejazi, Ehsan (Frontiers in Nutrition, 2024)
Objective: Preclinical evidences suggests that while fasting can reduce the side effects and toxicity of chemotherapy, it can make cancer cells more susceptible to chemotherapy. This study aimed to examine the effects of fasting mimicking diet (FMD) during neo-adjuvant chemotherapy in breast cancer (BC) patients.Methods: Forty-four newly diagnosed human epidermal growth factor receptor 2-negative (HER2-negative) patients with BC were randomized equally into two groups (22 each), to receive either a fasting mimicking diet (FMD) or their regular diet for 3 days prior to and during neoadjuvant chemotherapy. This FMD was repeated every three weeks for 8 cycles.Efficacy, toxicity, hematologic, metabolic, and inflammatory parameters were measured and compared.The occurrence of grade III vomiting and neutropenia in the control group was significantly higher than the FMD group (P= <0.001 and P= 0.04 respectively). Erythrocytes (P= 0.01) and neutrophils (P= 0.002) counts were significantly higher in FMD group compared to control group after cycle 8. There was a significant increase in median glucose and median insulin levels (P=0.01 and P=0.005, respectively) in the control group between baseline and after cycle 8. While, the median Insulin-like growth factor-1 (IGF1) (P= 0.006) and hs-CRP (P= 0.02) levels were significantly decreased in the FMD group. At the end of study (after cycle 8), the median glucose level was significantly higher in control group (P= 0.008), while the median hs-CRP level was significantly lower in FMD group (P= 0.01). The Miller and Payne pathological response 4/5 (90-100% tumor cell loss) and the radiologically complete or partial response, as measured by MRI or ultrasound before surgery occurred more frequently in FMD group compared to the controls (P= 0.01).FMD was well tolerated during chemotherapy and reduced toxicity of chemotherapy and also, had beneficial effects of some metabolic parameters.